Pengaruh Kualitas Layanan dan Citra Perusahaan terhadap Keunggulan Bersaing pada Shopeefood di Yogyakarta - Azel Thariq Esrito; Zulian Yamit (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to analyze the influence of service quality on competitive advantage at ShopeeFood in Yogyakarta and analyze the effect of corporate image on competitive advantage at ShopeeFood in Yogyakarta. The type of research used in this study is to use a survey research type. This research was conducted on ShopeeFood customers in Yogyakarta. As for the time of research in September 2022. The sample in this study was 97 respondents. Data analysis using multiple linear regression analysis. The results showed that service quality had a partial positive and significant effect on Competitive Advantage for Shopeefood customers in Yogyakarta and Corporate Image had a partial positive and significant effect on Competitive Advantage for Shopeefood customers in Yogyakarta.